Emotion anticipation and processing in depression: Behavioral, neural, and physiological reactivity - Magdalena Wlad; Wiebke Struckmann; Jonas Persson; Jörgen Rosén; David Fällmar; Robert Bodén; Malin Gingnell (European Psychiatry)
Abstract